Megagrazer loss drives complex landscape-scale biophysical cascades - Olli Hyvarinen; Mariska te Beest; Elizabeth le Roux; Graham I H Kerley; Robert Buitenwerf; Dave J Druce; Jiquan Chen; Linda Rapp; Joana Fernandes; Joris P G M Cromsigt (Environmental Research Letters)
Wild animals can modulate ecosystem-climate feedbacks, e.g. through impacts on vegetation and associated carbon dynamics. However, vegetation cover and composition also affect land surface albedo, which is an important component of the global energy budget. We currently know very little about the influence of wild animals on land surface albedo and the resulting climate forcing of these albedo changes. Leveraging a unique, ecosystem-scale, semi-experimental approach, we study how the local removals of the world’s largest, terrestrial grazer, white rhinoceros ( Ceratotherium simum ), affected the coupling between fire dynamics, woody encroachment and surface albedo in Hluhluwe–iMfolozi Park (HiP), South Africa. Our path analysis revealed that areas in the park where more rhinos had been removed showed a stronger increase in burnt area and woody encroachment compared to areas with fewer rhinos removed, which were both related to a decrease in surface albedo. Increasing burnt area was further associated with higher rates of woody encroachment, indirectly reinforcing the negative effect of rhino loss on albedo. Our study demonstrates that removals of megagrazers in HiP were related to complex ecosystem-wide cascades with measurable impacts on land cover and surface albedo and consequences on climate forcing. This highlights the importance of restoring functional ecosystems by reinstating trophic processes.